The Effect of Chest Physiotherapy and Static Bicycles on Improving Cardiovascular Function in Long Covid Cases: A Narrative Review - Norlinta, Siti Nadhir Ollin; Sari, Atika Kurnia (Ikatan Fisioterapi Indonesia, 2022)
Introduction: Long Covid is a term used to describe illness in people who have recovered from COVID-19 but continue to report long-term effects of the infection or have the typical symptoms for much longer than expected. Cardiovascular function aids the heart's and vascular system's ability and endurance in carrying out daily activities without significant fatigue. Physiotherapy contributes to the medical team by providing Chest physiotherapy and Static bicycle interventions to Long Covid patients. Because there has been no review research, it is necessary to investigate the effect of chest physiotherapy and static cycling on cardiovascular improvement in Long Covid patients. This research aims to determine the effect of two exercise therapies, namely chest physiotherapy and static bicycle to improve cardiovascular function in Long covid cases. Methodology: The research method used was narrative review with the PICO framework (Population/Patient/Problem, Intervention, Comparation, and Outcome). The journals were searched from 2 databases, namely Google Scholar and PubMed. Research findings: After screening the title and relevance of the abstract, as well as full text screening, 10 journals were obtained from the search for all two databases, proving the effect of Chest physiotherapy and Static bicycles on cardiovascular improvement in Long Covid patients. Conclusion: There is an effect of Chest Physiotherapy and Static bicycle on cardiovascular improvement in Long Covid patients.